X chromosome inactivation in a female carrier of a 1.28 Mb deletion encompassing the human X inactivation centre. (5th November 2017) - de Hoon, B.; Splinter, Erik; Eussen, B.; Douben, J. C. W.; Rentmeester, E.; van de Heijning, M.; Laven, J. S. E.; de Klein, J. E. M. M.; Liebelt, J.; Gribnau, J.
Abstract : X chromosome inactivation (XCI) is a mechanism specifically initiated in female cells to silence one X chromosome, thereby equalizing the dose of X-linked gene products between male and female cells. XCI is regulated by a locus on the X chromosome termed the X-inactivation centre (XIC). Located within the XIC is XIST, which acts as a master regulator of XCI. During XCI, XIST is upregulated on the inactive X chromosome and chromosome-wide cis spreading of XIST leads to inactivation. In mouse, the Xic comprises Xist and all cis -regulatory elements and genes involved in Xist regulation. The activity of the XIC is regulated by trans -acting factors located elsewhere in the genome: X-encoded XCI activators positively regulating XCI, and autosomally encoded XCI inhibitors providing the threshold for XCI initiation. Whether human XCI is regulated through a similar mechanism, involving trans -regulatory factors acting on the XIC has remained elusive so far. Here, we describe a female individual with ovarian dysgenesis and a small X chromosomal deletion of the XIC. SNP-array and targeted locus amplification (TLA) analysis defined the deletion to a 1.28 megabase region, including XIST and all elements and genes that perform cis -regulatory functions in mouse XCI. Cells carrying this deletion still initiate XCI on the unaffected X chromosome, indicating that XCI can be initiated in the presence of only one XIC. Our results indicate that the trans -acting factors required for XCI initiation are located outside the deletion, providing evidence that the regulatory mechanisms of XCI are conserved between mouse and human. This article is part of the themed issue 'X-chromosome inactivation: a tribute to Mary Lyon'.